Planning and Managing Sustainability in Tourism: Empirical Studies, Best-practice Cases and Theoretical Insights - (:unkn) unknown (My University, 2022)
This book provides a holistic approach to understand the challenges and opportunities related to the planning and management of sustainable development in tourism. The editors present a collection of empirical studies, best-practice cases, and theoretical discussions to draw insights on the economic, social, environmental, and political dimensions of sustainability. Specifically, using a range of case studies examining sustainability applications within various tourism industry sectors as well as different geographical regions, this book is of value to tourism policymakers, practitioners, academicians, and students, encouraging them to develop proactive behavior. This publication represents an up-to-date, innovative guide in helping readers understand the challenges facing sustainable tourism development and implementation as well as the potential opportunities for both developed and developing nations in pursuing sustainability goals in their tourism plans.
Keywords: Sustainable development in tourism; Sustainable development goals; United Nation’s agenda 2030; Tourism partnerships; Regional development; Circular economy; Community-based tourism; Tourist experiences; Inclusive cities